Optimizing Home-Based Education: A Comprehensive Investigation into the Efficacy of Play-Based Approaches for Enhancing Learning among Children with Autism - Hussein, Hussein (The Center for Disability Studies and Services Brawijaya University, 2024)
This research aims to investigate the effectiveness of play-based learning as an instructional strategy for homeschooling autistic children. The study utilises a qualitative approach to explore the experiences, perceptions, and outcomes of play-based learning interventions in the context of homeschooling. Through in-depth interviews, observations, and document analysis, the research seeks to gain a comprehensive understanding of the impact of play-based learning on the academic, social, and emotional development of autistic children within a homeschooling environment.